Minocycline Enhances the Antimicrobial Capacity of Unpolarized Macrophages Against Acinetobacter baumannii While Inducing an Anti-inflammatory Profile. (4th October 2017) - Guerra, Alberto; Rose, Warren; Andes, David R; Hematti, Peiman; Kao, Weiyuan John
Abstract: Background: Acinetobacter baumannii (AB) is a Gram-negative pathogen associated with high patient morbidity and mortality in nosocomial infections. Limited treatment options are available or in development for multidrug-resistant (MDR) AB, and therefore new approaches using older antibiotics are necessary. Minocycline (MIN) may hold potential in the treatment of complicated infections, as it has demonstrated a very high clinical success rate with MDR-AB microbiological eradication. MIN is known to affect the host immune response, and it may also have additional immunomodulatory effects as an antibiotic against MDR-AB. Methods: This study evaluates MIN effects on macrophage eradication of AB 5075, a well-characterized, virulent, MDR strain. We differentiated a human monocyctic cell line (THP-1) into unpolarized macrophages and subsequently treated the cells with different MIN doses or other antibiotic comparisons for 24 hours, including therapeutic concentrations found in serum and alveolar fluid during treatment. We then removed MIN and cultured AB at the exponential growth phase with the treated cells for 6 hours, and plated supernatant samples to determine bacterial growth potential followed by analysis of the co-culture supernatants for inflammatory cytokine production via ELISAs. Results: MIN pretreatment enhanced the antibacterial activity of unpolarized macrophages against AB with up to a 3-log reduction in bacterial load (Figure 1A), which was not observed when macrophages were pretreated with six different antibiotics (Figure 1B). MIN pretreatment correlated with an anti-inflammatory macrophage profile during AB co-culture (Figure 2), reducing production of IL-6, TNF-α, IL-1β, and MCP-1 in a dose-dependent manner. The enhanced antimicrobial activity of minocycline-treated macrophages was due to increased phagocytosis and the increased production of antimicrobial peptides. Conclusion: We demonstrate that minocycline can positively modulate the antibacterial and inflammatory profiles of macrophages against AB. This immunomodulation effect may partially explain the positive clinical success of MIN in complex patients with MDR-AB. Additional PK/PD studies will be important to optimize this effect. Disclosures: W. Rose, Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Speaker honorarium. Merck: Grant Investigator, Research grant. The Medicines Company: Speaker's Bureau, Speaker honorarium. Visante, Inc.: Consultant, Consulting fee. D. R. Andes, Paratek: Grant Investigator, Research support.